Description of a new species of Hemiberlesia Cockerell (Hemiptera: Coccomorpha: Diaspididae) from China, with a key to Hemiberlesia species known from China - Liu, Di; Feng, Jinian (Zootaxa, 2018)
The diagnostic characters of the genus Hemiberlesia Cockerell (Hemiptera: Coccoidea: Diaspididae) are reviewed. The adult female, adult male and all immature stages (except the male prepupa and pupa) of a new species, H. serrulata Liu & Feng sp. n., collected from Henan Province, China, are described and illustrated. A key is provided to identify the Hemiberlesia species known to occur in China.